Recent advances in personal protective equipment using nanotechnology as a shield against SARS-COV-2 - Montagner, Giane Engel; Rossato, Aline; Fagan, Solange Binotto; Gomes, Patrícia (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
COVID-19 is a disease caused by the SARS-CoV-2 coronavirus, and the use of personal protective equipment (PPE) has become essential against pandemics. This has led to many advances in facial masks and other types of PPE, using nanotechnology to improve antiviral properties and filterability. In this context, this study aimed at carrying out an integrative review regarding advances in personal protective equipment using nanotechnology to improve antiviral properties against SARS-CoV-2. Thus, 34 articles were retrieved from the Web of Science, Scopus, and PubMed databases, published until August 22, 2021. The main nanostructures used were nanofibers, carbon nanotubes, metallic nanoparticles, nanorods, nanowires, graphene, and C-dots, in the use of facial masks, air filters, and antiviral surfaces with functions such as antiviral/antimicrobial, reuse of personal protective equipment (PPE), self-feeding, whether by mechanical or solar action, hydrophobicity, and filtration efficiency, adjustable to the physical biotype of each individual and high breathability.